Knowledge about dietary fibres (KADF): development and validation of an evaluation instrument through structural equation modelling (SEM). (September 2016) - Guiné, R.P.F.; Duarte, J.; Ferreira, M.; Correia, P.; Leal, M.; Rumbak, I.; Barić, I.C.; Komes, D.; Satalić, Z.; Sarić, M.M.; Tarcea, M.; Fazakas, Z.; et al.
Abstract: Objectives: Because there is scientific evidence that an appropriate intake of dietary fibre should be part of a healthy diet, given its importance in promoting health, the present study aimed to develop and validate an instrument to evaluate the knowledge of the general population about dietary fibres. Study design: The present study was a cross sectional study. Methods: The methodological study of psychometric validation was conducted with 6010 participants, residing in 10 countries from three continents. The instrument is a questionnaire of self-response, aimed at collecting information on knowledge about food fibres. Exploratory factor analysis (EFA) was chosen as the analysis of the main components using varimax orthogonal rotation and eigenvalues greater than 1. In confirmatory factor analysis by structural equation modelling (SEM) was considered the covariance matrix and adopted the maximum likelihood estimation algorithm for parameter estimation. Results: Exploratory factor analysis retained two factors. The first was called dietary fibre and promotion of health (DFPH) and included seven questions that explained 33.94% of total variance (α = 0.852). The second was named sources of dietary fibre (SDF) and included four questions that explained 22.46% of total variance (α = 0.786). The model was tested by SEM giving a final solution with four questions in each factor. This model showed a very good fit in practically all the indexes considered, except for the ratio χ 2 /df. The values of average variance extracted (0.458 and 0.483) demonstrate the existence of convergent validity; the results also prove the existence of discriminant validity of the factors (r 2 = 0.028) and finally good internal consistency was confirmed by the values of composite reliability (0.854 and 0.787). Conclusions: This study allowed validating the KADF scale, increasing the degree of confidence in the information obtained through this instrument in this and in future studies. Graphical abstract: Highlights: Validation of an instrument using 6010 participants, from 10 countries. Exploratory factor analysis retained 11 from the 22 questions initially considered. The factor dietary fibre and promotion of health (DFPH) included seven questions (α = 0.852). The factor sources of dietary fibre (SDF) included four questions (α = 0.786). SEM modelling resulted in a validated two factor structure with four items in each factor.